2017
DOI: 10.1016/j.scitotenv.2017.07.113
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution of herbicide and insecticide residues in the water resources of the vineyard region of La Rioja (Spain)

Abstract: Pesticides are needed to maintain high production in the vineyard area of La Rioja (Spain), and monitoring their spatial distribution is a priority for preserving the quality of natural resources. Accordingly, the purpose of this work was to conduct a study to evaluate the presence and seasonal distribution of herbicide and insecticide residues in ground and surface waters in this region. The monitoring network comprised 12 surface waters and 78 groundwaters, covering the three subareas (63,593ha) into which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 41 publications
4
44
0
1
Order By: Relevance
“…The presence of neonicotinoids has been detected in various types of water reservoirs, including ditches, pools, ponds, mountain streams, rivers, periodic marshes, meltwater, and groundwater, effluents from WWTPs, and drinking water . The monitoring data were mainly available for four or less EU countries although neonicotinoids are widely used in Europe as Plant Protection Products (PPPs) and biocides.…”
Section: Occurrence Of Pesticides In Water In the Eu And Worldwidementioning
confidence: 99%
See 2 more Smart Citations
“…The presence of neonicotinoids has been detected in various types of water reservoirs, including ditches, pools, ponds, mountain streams, rivers, periodic marshes, meltwater, and groundwater, effluents from WWTPs, and drinking water . The monitoring data were mainly available for four or less EU countries although neonicotinoids are widely used in Europe as Plant Protection Products (PPPs) and biocides.…”
Section: Occurrence Of Pesticides In Water In the Eu And Worldwidementioning
confidence: 99%
“…Water pollution owing to the use of pesticides in agriculture is a priority issue that is currently of global concern . Surface water contamination by pesticides is usually linked to the farming season, and its effect could be more temporal than contamination of groundwater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of this limitation, studies have documented the presence of organochlorine, carbamate and organophosphate insecticides in Mediterranean bodies of water, noting that these compounds are generally found in low concentrations (ng L -1 ) or detected infrequently [8,31]. Finally, it is important to stress that the presence of insecticides in bodies of water constitutes a high risk to the biodiversity of these ecosystems, given that it has been demonstrated that elevated toxicity can have adverse effects on aquatic invertebrates in a short time period [32][33].…”
Section: Occurrence Of Insecticides In Surface Water Of Cachapoal Rivmentioning
confidence: 99%
“…Studies carried out in Asia [6], Europe [7][8] and the USA [9] show that pesticides and their degradation products are often detected in surface water, in some cases at levels exceeding the maximum individual limit (0.1 µg L -1 ) established by the European Commission (EC) for drinking water [10]. Therefore, various countries around the world have developed monitoring programs to evaluate the level of pesticide contamination in bodies of water, taking the measures necessary to minimize the impact of these substances on the environment and protect the quality of water resources [11].…”
Section: Introductionmentioning
confidence: 99%